Heat transfer to a gas from densely packed beds of cylindrical particles. (23rd November 2017) - Singhal, Arpit; Cloete, Schalk; Radl, Stefan; Quinta-Ferreira, Rosa; Amini, Shahriar
Graphical abstract: Highlights: Particle-resolved DNS applied in dense cylindrical particle packings is presented. A deep sensitivity analysis verifies the numerical accuracy of the method. A new heat transfer correlation for cylindrical particle packings is presented. New Ergun constants for pressure drop in cylindrical particle beds are presented. 95% confidence intervals are included to quantify uncertainty in the model. Abstract: Particle resolved direct numerical simulation (PR-DNS) has been used extensively to obtain closures for heat transfer from static particle arrays. However, most of the currently available closure models are valid for packings of spherical particles only. We present closure models for momentum and heat transfer in densely packed cylindrical particle assemblies of different aspect ratios (2, 4 and 6). Our packings are generated using the Discrete Element Method (DEM). Subsequently, the void space is meshed with a high quality computational grid, and steady-state DNS simulations are completed to provide insight into the local heat transfer and pressure drop characteristics. The variation observed in the values for the local heat transfer rates from our PR-DNS study implies the necessity of specifying confidence intervals when reporting a correlation for the corresponding Nusselt number. Our newly developed correlations are applicable to densely packed beds of cylindrical particles in the porosity range (0.405 < ε < 0.539), and allow the estimation of the variability of the Nusselt number.